Effective usage of renewal energy for engeering systems-optimization of solar energy in Indian oil and gas sector - Choudhary, Piyush (My University, 2018)
With fast rising energy demands and associated Carbon Emissions, the International Energy Agency (IEA) has projected a Renewable Energy (RE) technologies portfolio to reduce the emissions by the year 2050. It has been estimated that the global carbon emission can be reduced about 70% using the RE sources like Biomass, Solar, Wind, and Geothermal, directly for producing clean electricity or through their applications in various industries. The RE based technologies have been emerging very fast but also demands higher initial investments and latest research innovation. As per IEA reports around 28% of carbon reduction could be achieved by using non-biomass (15%) and biomass (8%) systems. Hence, the motivation of multidisciplinary studies (Solar Energy, Electricity Generation, and Bioenergy ) is the driving force for this thesis in the area of Environmental Sustainability. ONGC, the flagship national oil company under Government of India, has over-arching objective of the strategic sustainability for energy security. Carbon with as center of the business and sighting the implications, ONGC has been pursuing a low carbon high growth utilizing RE sources. The author employed at ONGC has undertaken multi-disciplinary research studies on PV technology,Concentrated Solar Power (CSP) and Microalgae Biomass to cater the electricityneeds, specific applications and finally to protect the environment. The three major aspects of this multidisciplinary research studies are as under: [1] Optimization of Solar Photovoltaic power at Natural Gas fed Captive Power Plant and development of a MATLAB based Despatcher Control system. [2] Utilizing Concentrated Solar Power technology for Crude Oil heating purpose and development of prototype hybrid model for real conditions. [3] Carbon Sequestration (Capture) using microalgae based innovative ‘State Of Art’ hybrid approach at Gas processing complex at ONGC India. In view of low carbon strategy a ‘Hybrid model’ has been conceptualized for oil and gas applications where the work has been outlined with two scenarios. First if carbon is emitted in the environment, the Carbon Capture approach has been thought and Second, to restrict the carbon emission, alternate sustainable solutions of energy has been explored.
Keywords: Renewable energy; Optimization of solar energy; Gas sector